STUDI FENOMENOLOGI: PERAN PENDIDIKAN EKONOMI PADA KELUARGA PEMILIK TOKO KELONTONG UNTUK MENUMBUHKAN JIWA WIRAUSAHA ANAK - Mareta Bunga Pratiwi; Hari Wahyono; Mareta Bunga Pratiwi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
The role of economic education in the family is the main foundation in shaping the economic behavior of a child. The part of economic education in the family of grocery store owners is expected to be able to develop entrepreneurial attitudes, abilities, and skills so that it has an impact on self-efficiency and able to increase entrepreneurial motivation. This study aims to help parents of business owners to try to find out and understand children's interests in entrepreneurship and how to instill an entrepreneurial spirit in children from an early age in their daily lives so that they can be helpful as a provision for future careers. The research method used is descriptive qualitative with phenomenological research type. The results showed that the application of family education in instilling an entrepreneurial spirit in the families of grocery store owners had been carried out well. The entrepreneurial spirit can be seen in implementing entrepreneurial values: honest, disciplined, confident, responsible, future-oriented, and willing to take risks. Three methods are considered effective in achieving these values: the habituation method, the coaching method, and the dialogue method. The results of the economic education process in instilling an entrepreneurial spirit can create children who can be rational, altruistic, and have economic morality.